2016
DOI: 10.21548/35-1-992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bottle Storage on Colour, Phenolics and Volatile Composition of Malvasia and Moscato White Wines

Abstract: The effect of bottle storage on the colour, phenolics and volatile composition of Malvasia and Muscat wines obtained from grapes grown in Sardinia was evaluated. Colour was evaluated by UV-VIS spectrophotometry and by tristimulus colorimetry. Polyphenols were analysed by UV-VIS spectrophotometry and HPLC-DAD. GC/MS was used to identify and quantify the content of free and bound volatile compounds. As expected, the absorbance values at 420 nm increased significantly for both wines during storage, due to oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…These reactions may have a negative or positive impact from the consumer's viewpoint [5,6]. Some authors have evaluated the factors related to wine aging, such as: the adverse influence of light and the influence of the bottle color on the evolution of the color and volatile composition of a wine [7][8][9][10][11][12]. However, studies to measure the effect of bottle colors on the profile of several families of phenolic compounds related to wine quality, such as flavanols, flavonols, phenolic acids, anthocyanins, and stilbenes, have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…These reactions may have a negative or positive impact from the consumer's viewpoint [5,6]. Some authors have evaluated the factors related to wine aging, such as: the adverse influence of light and the influence of the bottle color on the evolution of the color and volatile composition of a wine [7][8][9][10][11][12]. However, studies to measure the effect of bottle colors on the profile of several families of phenolic compounds related to wine quality, such as flavanols, flavonols, phenolic acids, anthocyanins, and stilbenes, have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that during maturation, oxygen promotes deep changes in the phenolic compounds. In particular, polyphenol oxidation determines the production of quinone, and their polymerization results in yellow-brown compounds responsible for wine browning reactions as aging proceeds [52][53][54]. As a consequence, Vin Santo can be characterized by a natural color that ranges from golden straw to intense amber [1].…”
Section: Sensory Analysismentioning
confidence: 99%
“…Vintages 2005 and 2006 were also described by the sensory descriptors baked apple odor (2005) and flavor (2006). Coherently, these vintages were also associated with higher concentrations of ethyl isovalerate and ethyl hexanoate (apple odor), as well as isoamyl acetate and diethyl succinate (apple flavor), which have been reported to be responsible for the perception of a fruity-apple odor [43,54,[56][57][58].…”
Section: Sensory Analysismentioning
confidence: 99%
“…In previous papers it was shown that the treatments with antioxidants on Feteasca regala variety induce detectable effects on the sensory profile [25] as well as on the general volatile profile (wine fingerprint) determined by an electronic nose based on CG principle [26]. However, the evolution of certain aroma compounds of white wines during bottle storage is of great interest [27,28] and this paper presents the differences among the volatile compounds found in the bottled wines obtained by various combinations of antioxidant treatments. The paper also attempts to identify specific compounds present in wines either from the grapes or as a result of fermentation, and to shed light on the types of antioxidant treatments which better preserve typical varietal volatile organic compounds.…”
Section: Introductionmentioning
confidence: 99%